The dynamics of folklore - Toelken, Barre, 1935-2018 (Utah State University Press, 1996)
One of the most comprehensive and widely praised introductions to folklore ever written. Toelken's discussion of the history and meaning of folklore is delivered in straightforward language, easily understood definitions, and a wealth of insightful and entertaining examples. Toelken emphasizes dynamism and variety in the vast array of folk expressions he examines, from "the biology of folklore," to occupational and ethnic lore, food ways, holidays, personal experience narratives, ballads, myths, proverbs, jokes, crafts, and others. Chapters are followed by bibliographical essay.